THE ROLE OF COLOCASIA ESCULENTA IN CANCER PREVENTION AND TREATMENT: A SYSTEMATIC REVIEW OF EPIDEMIOLOGICAL AND EXPERIMENTAL STUDIES - Fahmeeda S,; Prabu D,; Haripriya R,; Sindhu R,; Lubna Fathima,; Rajmohan M,; Dinesh Dhamodhar,; Banu Jothi A, (The Bioscan, 2026)
Cancer remains a leading global health challenge, with conventional treatments often causing severe side effects. Plant-based bioactives are increasingly explored for safer and cost-effective alternatives. Colocasia esculenta (taro), a traditional food crop, has been studied for its potential anticancer properties.